(untitled) (TAJ: Journal of Teachers Association, 2009)
Retrograde jejunogastric intussusception (RJGI) is a rare but potentially very serious complication of gastrojejunostomy or partial gastrectomy. Around 200 cases have been reported in literature till now. This paper reports two cases of RJGI of efferent loops developed 20 years and 10 years after gastrojejunostomy of a 70 years and 78 years old man respectively. Both the patients presented with sudden ab dominal pain and hematemesis. Upper GI-endoscopy established the diagnosis. On emergency basis laparotomy was done and intussusception was reduced through gastrotomy. Efferent loop was found viable in case no 01, but gangrenous in case no 02, where resection was done. In both the cases the efferent loops were fixed to anterior parietal wall to prevent recurrence. Postoperative recovery were uneventful except minor superficial wound infection in the second case. TAJ 2009; 22(1): 257-260